Upregulation of serum and glucocorticoid-regulated kinase 1 (SGK1) ameliorates doxorubicin-induced cardiotoxic injury, apoptosis, inflammation and oxidative stress by suppressing glucose regulated protein 78 (GRP78)-mediated endoplasmic reticulum stress. Issue 1 (1st January 2022) - Wang, Feng; Han, Lili
ABSTRACT: The clinical application of doxorubicin (Dox) in tumor chemotherapy is limited by time-dependent and dose-dependent cardiotoxicity. Hence, there is an urgent need to elucidate doxorubicin cardiotoxicity and to solve the difficult problem in clinical application. It has been verified that serum and glucocorticoid-regulated kinase 1 (SGK1) possess cardioprotective effects. Here, H9c2 cells were treated with 1 μM doxorubicin for 24 h to establish doxorubicin cardiotoxicity, so as to determine the biological role of SGK1 in doxorubicin cardiomyopathy and to elucidate the underlying molecular mechanism. SGK1 level in doxorubicin-treated H9c2 cells was assessed by performing Western blot assay and RT-qPCR. CCK-8 assay and TUNEL staining were employed to evaluate the cell viability and cell apoptosis. Besides, apoptosis-related proteins were measured by Western blot assay to analyze cell apoptosis. Additionally, the release of TNF-α, IL-1β, IL-6, and IL-10 and the levels of ROS, MDA, and SOD were detected to reflect inflammation and oxidative stress. Moreover, Western blot assay was adopted for determination of ERS-associated proteins. Results revealed that SGK1 was downregulated in doxorubicin-treated H9c2 cells. Upregulation of SGK1 alleviated doxorubicin-induced cardiotoxic injury, cell apoptosis, inflammation and oxidative stress in H9c2 cells. Moreover, SGK1 overexpression mitigated doxorubicin-induced ERS in H9c2 cells. The suppressing effects of SGK1 on doxorubicin-induced cardiotoxic injury, apoptosis, inflammation, oxidative stress and ERS in H9c2 cells were partially abolished upon GRP78 overexpression. To conclude, upregulation of SGK1 may alleviate doxorubicin cardiotoxicity by repressing GRP78-mediated ERS.